Enterprise Risk Management (ERM) in Malaysian high performance GLCs: a study of the status of implementation, the role of internal audit and the impact on organisational performance / Mohd Ariff Kasim - Kasim, Mohd Ariff (2011)
The primary research objectives of the study are to investigate the extent of the internal auditors' roles in the implementation of the Enterprise Risk Management (ERM) and to investigate the degree, nature and impact of the ERM implementation towards financial performance. This study mainly focuses on the High Performance (Government-Linked Companies) GLCs as these companies are the key players in the Malaysian economy. Careful and thorough steps were taken to develop the research instruments and perform all the relevant statistical analysis in achieving the research objectives. The primary data collection was through a questionnaire survey. The results of the stepwise and hierarchical multiple regressions indicated that the degree of the internal auditors' roles in the ERM could strengthen the relationship between the level of compliance by internal auditors towards the Professional Practice Framework (PPF) and the level of the ERM implementation. The internal audit level of compliance was also found to have a direct relationship towards the ERM implementation. The nature of the internal auditors' involvement in the ERM implementation was consistent with the recommendations in the Institute of Internal Auditors (IIA) position paper on the role of internal auditors in the ERM. The reality behind the adoption and implementation of the ERM is far from the ideal philosophy of the ERM. There is no strong association on the degree of the ERM implementation and the financial performance. The overall process of implementing the ERM demands for more serious attention. This study demonstrates the applicability of both the agency and stewardship theories in explaining the role of internal auditors in the ERM. Interestingly this study also provides comparative analysis between banking and non-banking industries. The internal auditors in the banking industry were found to perform more of their ERM assurance roles while the internal auditors in the non-banking industry were reported to perform almost equal proportion of their ERM assurance and consulting roles. The ERM is largely market-driven and most of the existing assessment tools have been developed by consultant. The present study had integrated the input from the internal audit professional body, internal auditors, review of previous works and relevant theoretical foundation. The study also served as among the first few attempt to bridge the gap in the literature by providing empirical support that significance to the body of knowledge.